Language Style in the International Diplomatic Meeting Between Donald Trump and Volodymyr Zelenskyy: A Sociolinguistics Study - Yumardila, Virlistyanti Dwi; Ervina CM Simatupang (International Journal of English Linguistics, Literature, and Education (IJELLE), 2025)
This study explores the language styles used in the international diplomatic meeting between U.S. President Donald Trump and Ukrainian President Volodymyr Zelenskyy. The objective of this research is to identify and classify the language styles employed during their meeting at the White House on February 28, 2025, published on the C-SPAN YouTube channel as well as to analyze the variations in language. The theories used in this study are Joos’s (1967) theory of language style and Holmes’s (2013) theory of sociolinguistic factors. Using a qualitative descriptive method, the researcher analyzed 29 utterances from diplomatic interactions, the result of the style of language style in their diplomatic meeting are frozen (20.7%), formal (27,6%), consultative (13,8%), casual (17,2%) and intimate (20,7%). The most dominat style in the international diplomatic meeting is formal. The study also highlights key sociolinguistic factors such as setting, participants, topic, and function that influence the choice of styles. These findings suggest that diplomatic language is both strategic and adaptive and is shaped by context, communicative purpose and audience. This research contributes to a deeper understanding of how political figures use language to manage perception, build rapport and reinforce diplomatic roles in international settings.